Pore‐scale evaluation of uranyl phosphate precipitation in a model groundwater system. Issue 2 (16th February 2013) - Fanizza, Michael F.; Yoon, Hongkyu; Zhang, Changyong; Oostrom, Martinus; Wietsma, Thomas W.; Hess, Nancy J.; Bowden, Mark E.; Strathmann, Timothy J.; Finneran, Kevin T.; Werth, Charles J.
Key Points In situ uranyl phosphate precipitation is fast on the time scale of remediation Ca2+ & SO42‐ affect uranyl phosphate precipitation rate and morphology Only chernikovite is formed, and it blocks pore spaces and reduces mixing